Nilai Tambah Pada Agroindustri Dodol Tomat (Studi Kasus Pada Usaha Kelompok Wanita Tani Mentari Desa Genteng, Kecamatan Sukasari, Kabupaten Sumedang) - Izati Rahmi; Lucyana Trimo (Journal of Food System & Agribusiness, 2019)
Genteng Village having its natural resources agricultural abundant, which is dominated by the various types plants horticulture one of them commodities are tomatoes. Agroindustry Dodol Tomat is one and only industry that processes tomato processing into refined products since 2017 by KWT Mentari. The purpose of this research is to describe the performance of agro-processing industry of dodol tomat, and to know added value obtained from processing of tomatoes until into become dodol tomat. This research uses qualitative design with case study technique. The data analysis methods that being used Hayami's added value analysis method. This research result indicates that the value added is received on the business ofÂ  dodol tomat amounting to Rp 11.340 per kilogram with a ratio of added value to the average output value of 37,8% per production process.Keywords: Tomatoes, Value Added, Performance of Agroindustry.